19 Anaesthetic management of staged separation of craniopagus conjoined twins. (22nd November 2019) - Jinks, Stephanie; King, Rumiko; Wilmshurst, Sally; Ong, Karbinh; Herod, Jane
Abstract : Description: Craniopagus conjoined twins represent 2% of all conjoined twins. 1 They occur in 1 per 2.5 million births and most do not survive, only a minority have anatomy suitable for surgical separation. Female craniopagus conjoined twins were born by caesarian section in Pakistan. Their shared skull was joined at the vertex but their brains appeared separate (figure 1 ). They were admitted to Great Ormond Street Hospital in August 2018, aged 17 months for a diagnostic workup. Innovative 3D stereolithographic models demonstrated that the twins had some arterial cross-over, shared superficial venous drainage and a common superior sagittal sinus. A staged separation process was planned over a 4-month period consisting of 3 steps, each presenting an extreme challenge for both surgeons and anaesthetists. Discussion: Anaesthesia for craniopagus conjoined twins is complex and experience is limited. This case required multiple pre-separation planning procedures and multiple stages to the surgery, with each twin requiring their own dedicated theatre team at each stage. Excellent teamwork was required throughout their care. The clinical challenges related to difficult airway management; understanding twin physiology and twin to twin transfusion syndrome; the preservation of blood vessels in small children having multiple major surgical procedures; massive blood transfusion; intraoperative arrhythmias and the impact of a long hospital stay. Successful separation was achieved in February 2019 and was only possible by exemplary collaboration between multidisciplinary teams, heightened situational awareness and outstanding communication. Reference: Stone JL, Goodrich JT. The craniopagus malformation: classification and implications for surgical separation. Brain 2006: 1084-1095.